Examining the spatial simulation and land-use reorganisation mechanism of agricultural suburban settlements using a cellular-automata and agent-based model: Six settlements in China. (September 2022) - Jiang, Xue; Li, Bingxin; Zhao, Hongyu; Zhang, Qiqi; Song, Xiaoya; Zhang, Haoran
Abstract: Peri-urban land-use development is an important representation of urban-rural system evolution in developing countries. As the modern agriculture industry promotes rapid spatial pattern changes, modelling this phenomenon is of considerable interest to urban planners and city managers. Several methods have been developed to simulate the dynamics of land-use changes. However, the complexity of such dynamics can impede the usefulness of simulation methods. In this paper, a new cellular-automata and agent-based model (CA-ABM) is introduced into the spatial simulation and reorganisation of peri-urban areas. This simulation and predictive model uses the geographic information system platform and cellular automata tool. The basic components of this dynamic bottom-up approach are the actors in land-use development. Using six settlements from plains, hilly, and mountainous areas as examples combined with field investigation, remote sensing images, official land-use planning, and other data, this study analysed land-use evolution under the influence of farmers, developers, and government agents to illustrate the spatial simulation and land-use reorganisation mechanism of agricultural suburban settlements. Compared with previous studies, this study shows that the CA-ABM can reflect the dynamic behaviour of agents and successfully fuses peri-urban settlement attributes and spatially accurate simulation. Simultaneously, the proposed spatial optimisation mechanism provides a reference for the spatial reorganisation of agricultural suburban zones worldwide. Highlights: This study analysed land-use evolution under the influence of various agents. Cellular automata and agent-based model was applied for the land-use simulation and prediction of peri-urban settlements. The CA-ABM can reflect the behaviours of various agents, including farmer agents, government agents and developer agents. Peri-urban settlement attribute information and spatially accurate simulation are fused.